2003
DOI: 10.1021/cm021794e
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Oxide and Chromium Oxide Coatings on Ceramic Fibers via MOCVD

Abstract: The overall strength and toughness of ceramic matrix composites is very much affected by the interfacial properties that govern the bonding between the reinforcing fibers and the matrix. The ability to control this interaction is very important. One method involves coating the ceramic fibers with an appropriate material. There is a definite advantage in using lower-temperature processes to produce the coatings:  fibers subjected to high-temperature coating processes are more prone to degradation due to microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The relative comparison of the EDS spectra of uncoated and coated particles indicates that, on these latter, an alumina film with carbon impurities was obtained. This result is in good accordance with previous works reported in literature, as already mentioned (Minkina, 1993;Nable et al, 2003).…”
Section: Fbcvd Of Alumina On Tungsten Powdersupporting
confidence: 94%
See 1 more Smart Citation
“…The relative comparison of the EDS spectra of uncoated and coated particles indicates that, on these latter, an alumina film with carbon impurities was obtained. This result is in good accordance with previous works reported in literature, as already mentioned (Minkina, 1993;Nable et al, 2003).…”
Section: Fbcvd Of Alumina On Tungsten Powdersupporting
confidence: 94%
“…However, several works, in which alumina coatings were obtained from aluminium acetylacetonate precursor in our range of temperature, i.e. 390-450 • C, have reported that obtained films exhibited orange-claret (Minkina, 1993), golden brown (Nable et al, 2003) or tan and dark tan (Nguyen et al, 2002) tints. These colours could be explained by an alumina film contamination due to carbon and pyrolysis by-products incorporation.…”
Section: Fbcvd Of Alumina On Tungsten Powdermentioning
confidence: 85%
“…7 Recent research in chromium-based composite oxides has revealed their functions in alkane oxidation, 8 ammoxidation, 9 dental materials, 10 etc. These oxides are typically prepared from thermal 11 and sol-gel 12 techniques, or as thin films from MO-CVD 13 and pulsed laser desorption (PLD). 14 Little is known about their syntheses from well-defined single-molecular sources, although there are a few intermetallic molecular complexes that could serve as precursors to mixed-metal or alloy materials.…”
Section: Introductionmentioning
confidence: 99%
“…Futhermore, some advanced processes such as the atomic layer deposition [13], chemical vapour deposition (CVD) [14], physical vapour deposition (PVD) [15], electrodeposition [16], and magnetron sputtering [17] techniques can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%